Marcus Vega doesn't speak Spanish - Cartaya, Pablo (Viking, 2018)
"After a fight at school leaves Marcus facing suspension, Marcus's mother takes him and his younger brother, who has Down syndrome, to Puerto Rico to visit relatives they do not remember or have never met, and while there Marcus starts searching for his father, who left their family ten years ago and is somewhere on the island"--Provided by publisher.